2006
DOI: 10.1007/s11090-006-9036-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Precursors and Plasma Parameters on Fullerene Synthesis in RF Thermal Plasma Reactor

Abstract: Synthesis of fullerenes from graphite powders of different grade was studied in a radiofrequency (RF) plasma reactor. Dependence of fullerene yield on the properties and feed rate of precursors and on the helium content of plasma gas was studied in details. The fullerene yield was influenced by the mean size and the thermal conductivity of graphite particles on the one hand, and the helium content of the gas phase on the other. Soot containing fullerene mixture of 5.9% was produced in best conditions found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Recently, it has been demonstrated that large-scale production of fullerenes is feasible by evaporating carbon-containing materials in RF induction thermal plasma reactors [11][12][13][14][15][16][17][18][19] (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been demonstrated that large-scale production of fullerenes is feasible by evaporating carbon-containing materials in RF induction thermal plasma reactors [11][12][13][14][15][16][17][18][19] (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Cota-Sanchez et al [15] extensively explored a fullerene synthesis process by an RF plasma jet (2)(3)(4)(5) to investigate the effect of the operating parameters on the fullerene formation, e.g., operating pressure, plate power, and carbon feed rate. Todorovic-Markovic et al reported the dependence of the fullerene yield on the properties of the graphite powder, e.g., mean aggregate size and thermal conductivity, as well as on the helium content in the plasma gas [17][18][19]. In order to investigate the influence of the plasma forming gas and operating pressure on the fullerene synthesis in an RF plasma process, Wang et al [11] developed a two-dimensional (2-D) model without considering the carbon particle injection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The argon and the helium were of 4.6 purity. Selection of working parameters was based on tests for the synthesis of nanoparticles using the same technique [9][10][11][12][13]27]. Helium was added both to the plasma and the carrier gas because of its high thermal conductivity and enthalpy, compared to other inert gases [11].…”
Section: Methodsmentioning
confidence: 99%
“…Titanium diboride (TiB 2 ) is a non-oxide refractory ceramic material with excellent properties such as high melting point (3225 °C), high hardness (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), high thermal (60-120 W/(m K)) and electrical conductivity (~10 5 S/cm), resistance to mechanical erosion and chemical corrosion. This combination of properties makes TiB 2 a candidate for high performance applications including wear resistant parts, metal melting crucibles, composite and electrode materials [1,2].…”
Section: Introductionmentioning
confidence: 99%